Pengaruh Perceived Ease Of Use, Usefulness, Dan Cashless Readiness Terhadap Cashless Society Mahasiswa Di Kota Batam - Yusca, Elmitha; Argo Putra Prima (Cattleya Darmaya Fortuna, 2026)
This study examines the effect of perceived ease of use, perceived usefulness, and cashless readiness on the adoption of a cashless society among university students. A quantitative approach was employed using a survey method with data collected from 93 student respondents. Data were analyzed using multiple linear regression. The results show that perceived ease of use, perceived usefulness, and cashless readiness have a positive and significant effect on cashless society adoption, both partially and simultaneously. Among these variables, perceived ease of use has the strongest influence. The findings indicate that the adoption of cashless payments is driven not only by system usability and perceived benefits but also by individual readiness to adopt digital payment technologies. This study contributes to the understanding of cashless society adoption by integrating perspectives from the Technology Acceptance Model and Technology Readiness concepts.